Intimate partner violence and help-seeking in the LGBT community - Carton, Hannah (2019)
This thesis provides a broad and diverse investigation into the field of intimate partner violence (IPV) within the LGBT community. A range of methods were used to explore issues in this field, these included a systematic review, a critical review of a psychometric measure used in this research, a primary quantitative investigation and a secondary mixed methods investigation. The chapters follow a ‘golden thread’ of the examination of psychological abuse, however they are diverse enough to remain independent studies in their own rights.